Main Drying and Wetting Curves of Soils: On Measurements, Prediction and Influence on Wave Propagation - ALBERS, Bettina (Engineering Transactions, 2015)
Depending on the initial degree of saturation of a soil different capillary pressure curves occur. If a sample is initially water saturated and then drained (process of drainage) the main drying curve results. On the other hand, if the sample is initially dry and water is supplied until saturation is reached (process of imbibition) the main wetting curve is the consequence. These two curves build a hysteresis loop. If after the first process the other is followed up (possibly a number of times), then inner hysteresis curves arise. The focus of this paper is the investigation of some aspects of the main drying curve (MDC) and the main wetting curve (MWC). Some methods of their measurement are discussed. Because of big differences in the capillary pressure for different degrees of saturation the measurement is laborious and time consuming and often application of more than one method is necessary. Consequently, often only the MDC is measured and the data is used to predict the MWC and inner curves. Exemplarily, one prediction method is shown and subsequently, for one soil type the resulting curves are used to calculate the wave speeds and attenuations of the appearing sound waves. The dependence of these wave features on frequency and saturation for the current example shows, that the hysteresis effect of the capillary pressure curve has only a slight ffect on the propagation of sound waves in partially saturated sand.